Efektivitas Media Pembelajaran Flipbook Terhadap Keterampilan Menulis Puisi Akrostik Siswa Kelas V Sekolah Dasar - Pramesthi, Natali Sonya Widya; Ismunadi, Ali (Universitas Muhammadiyah Magelang, 2026)
This study aims to determine the improvement and effectiveness of the use of flipbook learning media on the acrostic poetry writing skills of fifth grade students of SDN Sekaran 02, Semarang City. The background of the study is due to the still low acrostic poetry writing skills, which is caused by the lack of media that supports poetry writing skills. This study uses a quantitative method with an experimental design in the form of Nonequivalent Control Group Design. The research sample was 39 students from classes V A and V B. The experimental class was in class V B with 19 students, and the control class was in class V A with 20 students. Data collection techniques were carried out through tests, observations, and documentation. Data analysis used normality tests, homogeneity tests, hypothesis tests (Independent Sample T-tests), and N-Gain Tests. The results of the study showed that there were significant differences between the experimental class and the control class. This was proven through the Independent Sample T-test which showed a calculated tvalue > ttable (4.225 > 2.026). The average pretest to posttest score of the experimental class increased from 62.10 to 83.94. While in the control class, it initially increased from 60 to 70. In addition, the test criteria obtained by the experimental class were categorized as moderate with a score of 0.59, while in the control class, they were categorized as low with a score of 0.25. This finding confirms that the use of flipbook media is effective and improves the acrostic poetry writing skills of fifth grade students of SDN Sekaran 02.